Results of surgical treatment of ventricular septal defects with pulmonary hypertension. - John, S (1983)
Two hundred and twenty-five consecutive patients with interventricular septal defect and associated pulmonary hypertension have undergone corrective surgery at the Christian Medical College Hospital. The mean preoperative systolic pulmonary artery pressure was 70.5 (range 31-136) mm Hg and the calculated pulmonary vascular resistance ranged from 300 to 1680 dyn/s cm-5. A paracoronary right ventriculotomy was the approach of choice. Profound hypothermia and circulatory arrest were not used, even in 12 patients weighing under 10 kg. Among the older children and young adolescents there were 27 who had a calculated pulmonary vascular resistance of over 800 dyn/s cm-1 and their mortality was 22%, which is good when compared with that of other series. It is evident that both the early and the late death rate after surgery increase with the age of the patient, especially in those with associated pulmonary hypertension. In 69 patients studied after repair recatheterisation showed no residual defect by oximetry. The fall in the pulmonary artery pressures after surgery has been striking in most patients. The late death rate was 2.5%. The surviving patients are leading normal, active lives.